Statistical Mixture Design: Study of Solvent Performance in Temperature Controlled Microwave Assisted Extraction System on Antioxidant Properties of Nephrolepis biserrata (Schott.) Sw. frond Extract - Kormin, Faridah; Khan, Muhammad; Shafawati Mohd Shafie, Nor; Hamid Nour, Azhari; Mohd Yunus, Rosli (International Journal of Engineering and Technology, 2018)
Statistical simplex-centroid design mixtures of water, acetone, acetonitrile, ethanol were used to extract Nephrolepis biserrata (Schott.) SW. frond (NBF) using temperature controlled microwave extraction system (TCMES).Â The effects of different solvents and their mixtures on its antioxidant properties were studied. The result shows, the quality of extracted material is found to depend on the solvent proportions according to special cubic model of TPC, TFC and IC50. The binary and quaternary solvents are found to explain the superior extraction results as compared to single solvent for TPC, TFC and IC50.Â Â